A kind of silane modified polyether sealant and preparation method thereof

By introducing amino groups on nanoTiO2 and grafting flame retardant, the problem of insufficient flame retardant performance of silane-modified polyether gels is solved, and higher flame retardant and mechanical properties are achieved, and the resistance to UV aging is enhanced.

CN119081615BActive Publication Date: 2025-03-07NANJING QINGQI NEW MATERIAL TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411455103.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-03-07
Estimated Expiration
2044-10-17

AI Technical Summary

Technical Problem

Silane modified polyether glue is prone to flammability in high temperature or flame environments, and has insufficient flame retardant performance, making it difficult to meet the needs of fire-resistant and flame-retardant seals.

Method used

By introducing amino groups on nanoTiO2 and grafting the melamine-linoleic acid-POSS complex, guanidine aminophosphate, and nitrogen-phosphorus flame retardant on nanoTiO2, halogen-free flame retardant is prepared to improve the flame retardant performance of polyether gels.

Benefits of technology

It significantly improves the flame retardant and mechanical properties of silane-modified polyether sealant, delays the thermal degradation process, enhances the resistance to UV aging, and the halogen-free flame retardant is not easy to migrate and precipitate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005090238880000111
    Figure BDA0005090238880000111
  • Figure BDA0005090238880000121
    Figure BDA0005090238880000121
Patent Text Reader

Abstract

The invention discloses a silane-modified polyether sealant and a preparation method thereof. The invention belongs to the technical field of sealants. The invention prepares a product which is not only environmentally friendly but also has good adhesion and coating properties, and is weather-resistant and durable through the preferred combination of various components. The preparation method of the invention has the characteristics of simple process and safety, and the prepared product can be used for bonding and sealing in the fields of construction, home decoration, transportation, equipment manufacturing, etc.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sealants, and in particular to a silane-modified polyether sealant and a preparation method thereof. Background Art

[0002] Silane-modified polyether adhesive has the advantages of both silicone adhesive and polyurethane adhesive, with wide adhesion, low VOC emissions, paintability and other characteristics. Its curing mechanism is similar to that of silicone adhesive, both of which are moisture-curing types, relying on the hydrolysis of alkoxy groups in the terminal silane groups to form hydroxyl groups, and then forming a cross-linked network structure through condensation of the terminal hydroxyl groups. Currently, silane-modified polyether adhesive has been widely used in construction, rail transit, automobiles, interior decoration and other industries.

[0003] Fire-retardant sealing is often required in assembled doors and windows or displacement joints, as well as in electronic and electrical products in industrial applications and in the field of transportation. Silane-modified polyether adhesive has certain market potential. The flame retardant properties of polyether adhesive itself are poor and it is easy to burn when exposed to open flames or high temperatures.

[0004] Chinese patent document CN114015399A discloses a high-strength flame-retardant two-component silane-modified polyether adhesive and a preparation method thereof, wherein the polyether adhesive comprises component A and component B, wherein component A is composed of MS-polymer prepolymer, reinforcing filler A, thixotropic agent, flame retardant, plasticizer, light stabilizer and ultraviolet light absorber, and component B is composed of reinforcing filler B, plasticizer and organic tin catalyst. The invention significantly increases the tensile strength and tensile bonding strength of the product and improves the mechanical strength of the product by adjusting the types and proportions of MS-polymer prepolymer and reinforcing filler. At the same time, a flame retardant composite composed of a phosphorus-nitrogen mixed intumescent flame retardant and aluminum hydroxide is used to improve the flame retardant properties of the silane-modified polyether adhesive, so that the product has a good flame retardant effect, and the flame retardant properties reach V-0 level. The phosphorus-nitrogen mixed intumescent flame retardant and ultraviolet light absorber in the invention are small organic molecules, which are easy to migrate and precipitate from the polyether, thereby affecting its flame retardant and anti-aging properties. Summary of the invention

[0005] The main purpose of the present invention is to provide a silane-modified polyether sealant, which can improve the flame retardant performance of the polyether sealant by adding a special halogen-free flame retardant, which is not easy to migrate and precipitate.

[0006] To achieve the above object, the present invention provides a silane-modified polyether sealant, comprising the following components in parts by weight: 20-40 parts of silane-modified polyether resin, 5-10 parts of plasticizer, 1-3 parts of dewatering agent, 0.5-1 parts of thixotropic agent, 0.1-1 parts of catalyst, and 20-30 parts of halogen-free flame retardant.

[0007] Preferably, the plasticizer is diisodecyl phthalate and / or diisononyl phthalate.

[0008] Preferably, the dehydrating agent is at least one of vinyltrimethoxysilane, 3-isocyanatepropyltrimethoxysilane, anhydrous calcium chloride and calcium oxide.

[0009] Preferably, the thixotropic agent is carbon black and / or polyamide wax.

[0010] Preferably, the catalyst is at least one of dibutyltin dilaurate, monobutyltin triisooctoate, dihydroxybutyltin chloride, and stannous octoate.

[0011] Preferably, the preparation method of the halogen-free flame retardant is as follows:

[0012] S1: adding nano-TiO2 to ethanol aqueous solution, ultrasonically treating for 10-15 min, adding (3-aminopropyl)triethoxysilane, heating to 40-60°C, reacting for 3-5 h, cooling, filtering, collecting solids, washing and drying the solids to obtain amino-modified nano-TiO2;

[0013] S2: Mix melamine and chloroform and stir evenly, add linoleic acid, 1-ethyl-(3-dimethylaminopropyl)carbodiimide and citrate buffer, then stir and react at 40-60° C. for 4-6 hours, and evaporate the solvent under reduced pressure to obtain a linoleic acid-melamine complex; mix the linoleic acid-melamine complex and melamine and stir evenly, add vinyl POSS and dibenzoyl peroxide, heat and react at 60-100° C., and evaporate the solvent under reduced pressure to obtain a melamine-linoleic acid-POSS complex;

[0014] S3: In a nitrogen atmosphere, salicylaldehyde, triethylamine and ethyl acetate are mixed and stirred until salicylaldehyde is completely dissolved to obtain a mixed solution. Diphenylphosphinoyl chloride is dissolved in ethyl acetate at 0-10°C and then added dropwise to the mixed solution. After the addition is completed, the temperature is raised to 50-80°C for reaction for 20-24h. After the reaction is completed, the mixture is cooled, filtered, and the filtrate is collected. The filtrate is washed with saturated brine for 2-3 times, then dried with anhydrous calcium chloride overnight, filtered, and the residue obtained after the filtrate is evaporated under reduced pressure to remove the solvent is dissolved in anhydrous ethanol, p-aminophenol is added, the mixture is reacted at 40-60°C for 4-6h, cooled, and the solvent is evaporated under reduced pressure to obtain a nitrogen-phosphorus flame retardant;

[0015] S4: adding amino nano-TiO2, aminophosphoric acid guanidine, epichlorohydrin, melamine-linoleic acid-POSS complex, and nitrogen-phosphorus flame retardant to N,N-dimethylformamide, stirring and mixing evenly, reacting at 50-80°C for 4-6h, after the reaction is completed, filtering, collecting the solids and drying them to obtain a halogen-free flame retardant.

[0016] Preferably, in step S1, the mass ratio of nano-TiO2 to (3-aminopropyl)triethoxysilane is 20-30:1-3.

[0017] Preferably, in step S2, the mass ratio of melamine, linoleic acid, 1-ethyl-(3-dimethylaminopropyl)carbodiimide, and vinyl POSS is 1-2:0.5-1.5:0.5-0.8:3-5.

[0018] Preferably, in step S3, the mass ratio of salicylaldehyde, diphenylphosphinoyl chloride and p-aminophenol is 3-5:2-3:1-2.

[0019] Preferably, in step S4, the mass ratio of the amination nano-TiO2, aminophosphoric acid guanidine, epichlorohydrin, melamine-linoleic acid-POSS composite, and nitrogen-phosphorus flame retardant is 8-10:3-5:10-15:2-3:3-5.

[0020] The present invention introduces an amino group on nano-TiO2, and then grafts melamine-linoleic acid-POSS complex, aminophosphoric acid guanidine, and nitrogen-phosphorus flame retardant on nano-TiO2 by chemical grafting under the action of epichlorohydrin, thereby improving the dispersion of nano-TiO2 in polyether sealant, which is beneficial to improving the mechanical properties and flame retardant properties of polyether glue. Melamine and diphenylphosphoryl chloride are nitrogen-based and phosphorus-based flame retardants, respectively, but their flame retardant properties are not high. The inventor introduces linoleic acid with a relatively long hydrophobic alkyl long-chain structure on melamine to improve the water repellency of the sealant and protect the sealed parts from moisture erosion. The introduction of carbon-carbon double bonds is beneficial to the subsequent addition reaction with vinyl POSS. By introducing linoleic acid and POSS on melamine, the thermal stability and water repellency of melamine can be significantly improved, the thermal degradation process of polyether glue can be delayed, and its flame retardant properties can be improved. By modifying diphenylphosphoryl chloride with hydroquinone, the diphenylphosphoryl chloride molecules can be At the same time, it contains flame retardant elements such as nitrogen and phosphorus, which can decompose acidic substances during combustion and promote the formation of a carbon layer on the surface of the substrate. The nano-TiO2, melamine-linoleic acid-POSS composite, aminophosphoric acid guanidine, and nitrogen-phosphorus flame retardant are all flame retardant. When introduced into the polyether adhesive, the flame retardant properties of the polyether adhesive are synergistically enhanced. The grafted nano-TiO2 is easier to cross-link with other components to produce a more complex and dense cross-linked structure. The halogen-free flame retardant is not easy to migrate out of the polyether adhesive matrix, thereby improving the mechanical and flame retardant properties of the polyether adhesive. The grafted nano-TiO2 also gives the polyether adhesive a certain anti-ultraviolet aging performance.

[0021] The present invention also discloses a method for preparing the silane-modified polyether sealant, comprising the following steps:

[0022] Weigh each component according to the formula, mix the plasticizer, dehydrating agent, thixotropic agent, ultraviolet absorber and halogen-free flame retardant evenly under N2 atmosphere, heat to 90-100°C, vacuum dry for 1-3h, then cool to 40-50°C, add silane-modified polyether resin, stir evenly, add catalyst and mix evenly to obtain the silane-modified polyether sealant.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] 1. The silane-modified polyether sealant of the present invention is prepared by optimizing the combination of the components, so that the product is not only environmentally friendly, but also has good adhesion, coating, weather resistance and durability; the preparation method of the present invention has the characteristics of simple process and safety, and the prepared product can be used for bonding and sealing in the fields of construction, home decoration, transportation, equipment manufacturing, etc.

[0025] 2. The present invention introduces amino groups into nano-TiO2, and then grafts POSS-melamine complex, aminophosphoric acid guanidine and nitrogen-phosphorus flame retardant onto nano-TiO2 by chemical grafting under the action of epichlorohydrin, thereby improving the dispersion of nano-TiO2 in polyether sealant. Its special molecular structure can produce higher functionality and more cross-linking points during the curing process of polyether sealant, forming stronger restrictions on molecular chains, which is conducive to deepening the cross-linking depth of the tape and inhibiting the flow of colloids, accelerating curing, thereby shortening the surface drying time, further improving the bonding effect, and improving the mechanical properties and flame retardant properties of the polyether sealant. DETAILED DESCRIPTION

[0026] The sources of some raw materials in the examples of the present invention are as follows. Unless otherwise specified, the raw materials used in the examples can be obtained from conventional commercial channels or can be prepared by conventional methods.

[0027] The sources of some raw materials used in the present invention are as follows:

[0028] Silane-modified polyether resin, model 303H, purchased from Kaneka Chemical Co., Ltd., Japan, with a molecular weight of 5000 and a viscosity of 20000 cps.

[0029] Nano-TiO2, rutile type, with a particle size of 5 nm, was purchased from Hebei Jipin New Materials Co., Ltd.

[0030] Vinyl POSS was purchased from Angxing New Carbon Materials Changzhou Co., Ltd.

[0031] Example 1

[0032] A method for preparing a silane-modified polyether sealant comprises the following steps:

[0033] Under N2 atmosphere, 80g of diisodecyl phthalate, 20g of 3-isocyanatepropyltrimethoxysilane, 8g of polyamide wax and 250g of halogen-free flame retardant were mixed evenly, heated to 100°C, vacuum dried for 2h, and then cooled to 45°C. 300g of silane-modified polyether resin was added and stirred evenly, and then 6g of dibutyltin dilaurate was added and mixed evenly to obtain the silane-modified polyether sealant.

[0034] The preparation method of the halogen-free flame retardant is as follows:

[0035] S1: 25.8 g of nano-TiO2 was added to 300 mL of 50 wt% ethanol aqueous solution, and ultrasonic treatment was performed for 15 min. 2 g of (3-aminopropyl) triethoxysilane was added, and the mixture was heated to 50°C, reacted for 4 h, cooled, filtered, and the solid was collected. The solid was washed and dried to obtain amino-modified nano-TiO2.

[0036] S2: 15.6 g of melamine and 200 mL of chloroform were mixed and stirred evenly, 12.3 g of linoleic acid, 7.5 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide and 40 mL of citrate buffer were added, and then the mixture was stirred at 50° C. for 46 h, and the solvent was evaporated under reduced pressure to obtain a linoleic acid-melamine complex; the linoleic acid-melamine complex and 500 mL of chloroform were mixed and stirred evenly, 40.3 g of vinyl POSS and 5.8 g of dibenzoyl peroxide were added, and the mixture was heated at 80° C. for 6 h, and the solvent was evaporated under reduced pressure to obtain a melamine-linoleic acid-POSS complex;

[0037] S3: Under a nitrogen atmosphere, 41 g of salicylaldehyde, 30.3 g of triethylamine and 500 mL of ethyl acetate were mixed and stirred until salicylaldehyde was completely dissolved to obtain a mixed solution. At 0°C, 25.5 g of diphenylphosphinoyl chloride was dissolved in 200 mL of ethyl acetate and then added dropwise to the mixed solution. After the addition was completed, the temperature was raised to 60°C and reacted for 24 hours. After the reaction was completed, the mixture was cooled, filtered and the filtrate was collected. The filtrate was washed with saturated brine for 3 times, then dried with anhydrous calcium chloride overnight, filtered, and the residue obtained after the filtrate was evaporated under reduced pressure to remove the solvent was dissolved in 300 mL of anhydrous ethanol, 18 g of p-aminophenol was added, the mixture was reacted at 50°C for 5 hours, cooled, and the solvent was evaporated under reduced pressure to obtain a nitrogen-phosphorus flame retardant.

[0038] S4: Add 9 g of amino-modified nano-TiO2, 4.2 g of aminophosphoric acid guanidine, 13 g of epichlorohydrin, 2.5 g of melamine-linoleic acid-POSS complex, and 4 g of nitrogen-phosphorus flame retardant into 200 mL of N,N-dimethylformamide, stir and mix evenly, react at 60°C for 5 h, and after the reaction is completed, filter, collect the solids, and dry to obtain a halogen-free flame retardant.

[0039] Example 2

[0040] A method for preparing a silane-modified polyether sealant comprises the following steps:

[0041] Under N2 atmosphere, 100g of diisodecyl phthalate, 30g of 3-isocyanatepropyltrimethoxysilane, 10g of polyamide wax and 300g of halogen-free flame retardant were mixed evenly, heated to 100°C, vacuum dried for 3h, and then cooled to 50°C, 400g of silane-modified polyether resin was added and stirred evenly, and then 10g of dibutyltin dilaurate was added and mixed evenly to obtain the silane-modified polyether sealant.

[0042] The preparation method of the halogen-free flame retardant is as follows:

[0043] S1: 29.8 g of nano-TiO2 was added to 300 mL of 50 wt% ethanol aqueous solution, and ultrasonic treatment was performed for 10 min. 3 g of (3-aminopropyl) triethoxysilane was added, and the mixture was heated to 60°C, reacted for 5 h, cooled, filtered, and the solid was collected. The solid was washed and dried to obtain amino-modified nano-TiO2.

[0044] S2: 10.2 g of melamine and 200 mL of chloroform were mixed and stirred evenly, 5.6 g of linoleic acid, 5 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide and 40 mL of citrate buffer were added, and then stirred and reacted at 40° C. for 6 h, and the solvent was evaporated under reduced pressure to obtain a linoleic acid-melamine complex; the linoleic acid-melamine complex and 500 mL of chloroform were mixed and stirred evenly, 30.3 g of vinyl POSS and 4.3 g of dibenzoyl peroxide were added, and the reaction was heated at 60° C. for 6 h, and the solvent was evaporated under reduced pressure to obtain a melamine-linoleic acid-POSS complex;

[0045] S3: Under a nitrogen atmosphere, 30.2 g of salicylaldehyde, 15.3 g of triethylamine and 500 mL of ethyl acetate were mixed and stirred until salicylaldehyde was completely dissolved to obtain a mixed solution. At 10°C, 20.5 g of diphenylphosphinoyl chloride was dissolved in 200 mL of ethyl acetate and then added dropwise to the mixed solution. After the addition was completed, the temperature was raised to 60°C for reaction for 24 h. After the reaction was completed, the mixture was cooled, filtered and the filtrate was collected. The filtrate was washed with saturated brine for 3 times, then dried with anhydrous calcium chloride overnight, filtered, and the residue obtained after the filtrate was evaporated under reduced pressure to remove the solvent was dissolved in 300 mL of anhydrous ethanol, 10.3 g of p-aminophenol was added, the mixture was reacted at 40°C for 5 h, and then cooled. The solvent was evaporated under reduced pressure to obtain a nitrogen-phosphorus flame retardant.

[0046] S4: Add 8g of amino-modified nano-TiO2, 3.2g of aminophosphoric acid guanidine, 10.5g of epichlorohydrin, 2g of melamine-linoleic acid-POSS complex, and 3g of nitrogen-phosphorus flame retardant into 200mL of N,N-dimethylformamide, stir and mix evenly, react at 80°C for 4h, and after the reaction is completed, filter, collect the solids and dry them to obtain a halogen-free flame retardant.

[0047] Example 3

[0048] A method for preparing a silane-modified polyether sealant comprises the following steps:

[0049] Under N2 atmosphere, 50g of diisodecyl phthalate, 10g of 3-isocyanatepropyltrimethoxysilane, 5g of polyamide wax and 200g of halogen-free flame retardant were mixed evenly, heated to 90°C, vacuum dried for 1h, and then cooled to 40°C. 200g of silane-modified polyether resin was added and stirred evenly, and then 1.5g of dibutyltin dilaurate was added and mixed evenly to obtain the silane-modified polyether sealant.

[0050] The preparation method of the halogen-free flame retardant is as follows:

[0051] S1: 20.5 g of nano-TiO2 was added to 300 mL of 50 wt% ethanol aqueous solution, and ultrasonic treatment was performed for 10 min. 1 g of (3-aminopropyl) triethoxysilane was added, and the mixture was heated to 40°C, reacted for 3 h, cooled, filtered, and the solid was collected. The solid was washed and dried to obtain amino-modified nano-TiO2.

[0052] S2: 19.9 g of melamine and 200 mL of chloroform were mixed and stirred evenly, 15 g of linoleic acid, 8 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide and 40 mL of citrate buffer were added, and then stirred and reacted at 60° C. for 4 h, and the solvent was evaporated under reduced pressure to obtain a linoleic acid-melamine complex; the linoleic acid-melamine complex and 500 mL of chloroform were mixed and stirred evenly, 50 g of vinyl POSS and 6.5 g of dibenzoyl peroxide were added, and the mixture was heated and reacted at 100° C. for 6 h, and the solvent was evaporated under reduced pressure to obtain a melamine-linoleic acid-POSS complex;

[0053] S3: Under a nitrogen atmosphere, 50 g of salicylaldehyde, 35.2 g of triethylamine and 500 mL of ethyl acetate were mixed and stirred until salicylaldehyde was completely dissolved to obtain a mixed solution. At 0°C, 30 g of diphenylphosphinoyl chloride was dissolved in 200 mL of ethyl acetate and then added dropwise to the mixed solution. After the addition was completed, the temperature was raised to 60°C for reaction for 24 h. After the reaction was completed, the mixture was cooled, filtered and the filtrate was collected. The filtrate was washed with saturated brine for 3 times, then dried with anhydrous calcium chloride overnight, filtered, and the residue obtained after the filtrate was evaporated under reduced pressure to remove the solvent was dissolved in 300 mL of anhydrous ethanol, 20 g of p-aminophenol was added, the mixture was reacted at 50°C for 5 h, and then cooled. The solvent was evaporated under reduced pressure to obtain a nitrogen-phosphorus flame retardant.

[0054] S4: Add 10g of amino-modified nano-TiO2, 5g of aminophosphoric acid guanidine, 15g of epichlorohydrin, 3g of melamine-linoleic acid-POSS complex, and 5g of nitrogen-phosphorus flame retardant into 200mL of N,N-dimethylformamide, stir and mix evenly, react at 50°C for 5h, and after the reaction is completed, filter, collect the solids and dry them to obtain a halogen-free flame retardant.

[0055] Comparative Example 1

[0056] A method for preparing a silane-modified polyether sealant is similar to Example 1, except that no nitrogen-phosphorus flame retardant is added, and specifically comprises the following steps:

[0057] Under N2 atmosphere, 80g of diisodecyl phthalate, 20g of 3-isocyanatepropyltrimethoxysilane, 8g of polyamide wax and 250g of halogen-free flame retardant were mixed evenly, heated to 100°C, vacuum dried for 2h, and then cooled to 45°C. 300g of silane-modified polyether resin was added and stirred evenly, and then 6g of dibutyltin dilaurate was added and mixed evenly to obtain the silane-modified polyether sealant.

[0058] The preparation method of the halogen-free flame retardant is as follows:

[0059] S1: 25.8 g of nano-TiO2 was added to 300 mL of 50 wt% ethanol aqueous solution, and ultrasonic treatment was performed for 15 min. 2 g of (3-aminopropyl) triethoxysilane was added, and the mixture was heated to 50°C, reacted for 4 h, cooled, filtered, and the solid was collected. The solid was washed and dried to obtain amino-modified nano-TiO2.

[0060] S2: 15.6 g of melamine and 200 mL of chloroform were mixed and stirred evenly, 12.3 g of linoleic acid, 7.5 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide and 40 mL of citrate buffer were added, and then the mixture was stirred at 50° C. for 46 h, and the solvent was evaporated under reduced pressure to obtain a linoleic acid-melamine complex; the linoleic acid-melamine complex and 500 mL of chloroform were mixed and stirred evenly, 40.3 g of vinyl POSS and 5.8 g of dibenzoyl peroxide were added, and the mixture was heated at 80° C. for 6 h, and the solvent was evaporated under reduced pressure to obtain a melamine-linoleic acid-POSS complex;

[0061] S3: Add 9g of amino-modified nano-TiO2, 4.2g of aminophosphoric acid guanidine, 13g of epichlorohydrin, and 2.5g of melamine-linoleic acid-POSS complex into 200mL of N,N-dimethylformamide, stir and mix evenly, react at 60°C for 5h, and after the reaction is completed, filter, collect the solids and dry them to obtain a halogen-free flame retardant.

[0062] Comparative Example 2

[0063] A method for preparing a silane-modified polyether sealant is similar to Example 1, except that no melamine-linoleic acid-POSS complex is added, and specifically comprises the following steps:

[0064] Under N2 atmosphere, 80g of diisodecyl phthalate, 20g of 3-isocyanatepropyltrimethoxysilane, 8g of polyamide wax and 250g of halogen-free flame retardant were mixed evenly, heated to 100°C, vacuum dried for 2h, and then cooled to 45°C. 300g of silane-modified polyether resin was added and stirred evenly, and then 6g of dibutyltin dilaurate was added and mixed evenly to obtain the silane-modified polyether sealant.

[0065] The preparation method of the halogen-free flame retardant is as follows:

[0066] S1: 25.8 g of nano-TiO2 was added to 300 mL of 50 wt% ethanol aqueous solution, and ultrasonic treatment was performed for 15 min. 2 g of (3-aminopropyl) triethoxysilane was added, and the mixture was heated to 50°C, reacted for 4 h, cooled, filtered, and the solid was collected. The solid was washed and dried to obtain amino-modified nano-TiO2.

[0067] S2: Under a nitrogen atmosphere, 41 g of salicylaldehyde, 30.3 g of triethylamine and 500 mL of ethyl acetate were mixed and stirred until salicylaldehyde was completely dissolved to obtain a mixed solution. At 0°C, 25.5 g of diphenylphosphinoyl chloride was dissolved in 200 mL of ethyl acetate and then added dropwise to the mixed solution. After the addition was completed, the temperature was raised to 60°C and reacted for 24 hours. After the reaction was completed, the mixture was cooled, filtered and the filtrate was collected. The filtrate was washed with saturated brine for 3 times, then dried with anhydrous calcium chloride overnight, filtered, and the residue obtained after the filtrate was evaporated under reduced pressure to remove the solvent was dissolved in 300 mL of anhydrous ethanol, 18 g of p-aminophenol was added, the mixture was reacted at 50°C for 5 hours, cooled, and the solvent was evaporated under reduced pressure to obtain a nitrogen-phosphorus flame retardant.

[0068] S3: Add 9g of amino-modified nano-TiO2, 4.2g of aminophosphoric acid guanidine, 13g of epichlorohydrin, and 4g of nitrogen-phosphorus flame retardant into 200mL of N,N-dimethylformamide, stir and mix evenly, react at 60°C for 5h, and after the reaction is completed, filter, collect the solids and dry them to obtain a halogen-free flame retardant.

[0069] Test Case

[0070] The silane-modified polyether sealants prepared in Comparative Examples 1-2 and Examples 1-3 were used as test objects, and performance tests were performed on them. The test conditions were standard conditions, with a temperature of 23±1° C. and a humidity of 50%±5%.

[0071] Dry time:

[0072] Tensile strength measurement: The sealant was evenly coated on a mold with a thickness of 2 mm, cured at room temperature for 7 days, and the tensile strength was tested according to GB / T528-2009;

[0073] Light aging test: refer to GB / T16422.3-2022 standard, average irradiance 0.5W / m 2 The light aging test was carried out at a plate temperature of 65°C and a test time of 1000 h. After aging, the sample was air-dried at room temperature for 24 h and its tensile strength was measured.

[0074] Flame retardancy test: prepare a film with a width of 5mm and a thickness of 0.5mm, burn it with the outer flame of an alcohol lamp, and measure the burning condition after leaving the fire; test the flame retardancy level according to GB / T10707-2008.

[0075] The test results are shown in Table 1:

[0076] Table 1 Silane modified polyether sealant performance test results

[0077]

[0078]

[0079] It can be seen from the experimental results in Table 1 that the silane-modified polyether sealant prepared in Example 1 of the present invention has a shorter surface drying time and better flame retardant and mechanical properties.

[0080] The above are only preferred embodiments of the present invention, and do not limit the patent scope of the present invention. For those skilled in the art, the present invention may have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the patent protection scope of the present invention.

Claims

1. A silane-modified polyether sealant, characterized in that: The invention comprises the following components in parts by weight: 20-40 parts of silane-modified polyether resin, 5-10 parts of plasticizer, 1-3 parts of dewatering agent, 0.5-1 parts of thixotropic agent, 0.1-1 parts of catalyst, and 20-30 parts of halogen-free flame retardant; The preparation method of the halogen-free flame retardant is as follows: S1: adding nano-TiO2 to ethanol aqueous solution, ultrasonically treating for 10-15 min, adding (3-aminopropyl)triethoxysilane, heating to 40-60°C, reacting for 3-5 h, cooling, filtering, collecting solids, washing and drying the solids to obtain amino-modified nano-TiO2; S2: Mix melamine and chloroform and stir evenly, add linoleic acid, 1-ethyl-(3-dimethylaminopropyl)carbodiimide and citrate buffer, then stir and react at 40-60° C. for 4-6 hours, and evaporate the solvent under reduced pressure to obtain a linoleic acid-melamine complex; mix the linoleic acid-melamine complex and melamine and stir evenly, add vinyl POSS and dibenzoyl peroxide, heat and react at 60-100° C., and evaporate the solvent under reduced pressure to obtain a melamine-linoleic acid-POSS complex; S3: In a nitrogen atmosphere, salicylaldehyde, triethylamine and ethyl acetate are mixed and stirred until salicylaldehyde is completely dissolved to obtain a mixed solution. Diphenylphosphinoyl chloride is dissolved in ethyl acetate at 0-10°C and then added dropwise to the mixed solution. After the addition is completed, the temperature is raised to 50-80°C for reaction for 20-24h. After the reaction is completed, the mixture is cooled, filtered, and the filtrate is collected. The filtrate is washed with saturated brine for 2-3 times, then dried with anhydrous calcium chloride overnight, filtered, and the residue obtained after the filtrate is evaporated under reduced pressure to remove the solvent is dissolved in anhydrous ethanol, p-aminophenol is added, the mixture is reacted at 40-60°C for 4-6h, cooled, and the solvent is evaporated under reduced pressure to obtain a nitrogen-phosphorus flame retardant; S4: adding aminated nano-TiO2, aminophosphoric acid guanidine, epichlorohydrin, melamine-linoleic acid-POSS complex, and nitrogen-phosphorus flame retardant to N,N-dimethylformamide, stirring and mixing evenly, reacting at 50-80°C for 4-6h, filtering after the reaction is completed, collecting the solids and drying them to obtain a halogen-free flame retardant; In the step S2, the mass ratio of melamine, linoleic acid, 1-ethyl-(3-dimethylaminopropyl)carbodiimide, and vinyl POSS is 1-2:0.5-1.5:0.5-0.8:3-5; In the step S3, the mass ratio of salicylaldehyde, diphenylphosphinoyl chloride and p-aminophenol is 3-5:2-3:1-2; In the step S4, the mass ratio of the amination nano-TiO2, aminophosphoric acid guanidine, epichlorohydrin, melamine-linoleic acid-POSS composite, and nitrogen-phosphorus flame retardant is 8-10:3-5:10-15:2-3:3-5.

2. The silane-modified polyether sealant according to claim 1, characterized in that: The plasticizer is diisodecyl phthalate and / or diisononyl phthalate.

3. The silane-modified polyether sealant according to claim 1, characterized in that: The dewatering agent is at least one of vinyl trimethoxy silane, 3-isocyanate propyl trimethoxy silane, anhydrous calcium chloride and calcium oxide.

4. The silane-modified polyether sealant according to claim 1, characterized in that: The thixotropic agent is carbon black and / or polyamide wax.

5. The silane-modified polyether sealant according to claim 1, characterized in that: The catalyst is at least one of dibutyltin dilaurate, monobutyltin triisooctoate, dihydroxybutyltin chloride and stannous octoate.

6. A method for preparing the silane-modified polyether sealant according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: weighing each component according to the formula, mixing the plasticizer, dehydrating agent, thixotropic agent, ultraviolet absorber and halogen-free flame retardant evenly under N2 atmosphere, heating to 90-100°C, vacuum drying for 1-3h, then cooling to 40-50°C, adding silane-modified polyether resin and stirring evenly, and then adding a catalyst and mixing evenly to obtain the silane-modified polyether sealant.

Citation Information

Patent Citations

  • High-strength flame-retardant two-component silane modified polyether adhesive and preparation method thereof

    CN114015399A

  • DOPO (9,10-Dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) derivative grafted siloxane flame retardant reaction type cable material and preparation method thereof

    CN107022142A

  • Preparation method of water-resistant soy protein adhesive

    CN108624285A